Викладання музики в Університеті св. Володимира (1834–1859 рр.) - Самчук, Т. (Український історичний збірник, 2015)
Досліджено систему викладання музики в Університеті Св. Володимира у період 1834–1859 рр. Проаналізовано й визначено роль та місце музики в системі класичної університетської освіти. Висвітлено подробиці викладання музики та церковного співу в Університеті Св. Володимира. Для досягнення мети були застосовані історико-порівняльний, історико-системний та ретроспективний методи. Висновки дослідження вказують на те, що музика була одним із компонентів університетської системи освіти та виконувала завдання мистецько-естетичного виховання студентів Університету Св. Володимира. Teaching of music in St. Vladimir University during the 1834–1859 years was researched in the article. The aim of this paper is to explore and analyze the quality of teaching music, the level of teacher training and also to reconstruct the timetables of music lesson for that period. The role and place of music in the educational system of the university were identified in the article. Historical and comparative, historical and systematic, retrospective methods were applied in carrying out the objectives. The conclusion of this research indicate that music was a component of educational system. This academic subject contributed to artistic and aesthetic development of students. The unknown archived documents are used in the research.